Pengaruh Kelekatan Terhadap Ekspresi Emosi dalam Relasi Pernikahan - Rena Latifa (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2015)
The purpose of this research is to explore: 1) the correlation between attachment style and emotional expression in a marital relationship, 2) the correlation between secure attachment style and positive emotional expression in a marital relationship, 3) the correlation between avoidant attachment style, 4) the correlation between anxiety and positive emotional expression. This study involved 58 person as participants. The results of this study demonstrated that there was a positive significant relationship between attachment style with the emotional expression in marital relationship. Attachment contribute 50.3% to the person positive emotions expression. The ability to express emotions in a positive way was increased if spouses had attachment for each other. This study also discovered that the most influential attachment style on the likelihood of a positive emotional expression is secure attachment styles. The more secure the person feeling to the spouse, the ability to express emotions in a positive way also increasing. Keywords: attachment style, emotional expression, marital relation